Winter's tail : how one little dolphin learned to swim again - Hatkoff, Juliana; Hatkoff, Craig; Hatkoff, Isabella (New York : Scholastic Press, 2009)
Recounts the true story of Winter, a dolphin who lost her tail and had to relearn how to swim using a specially-created prosthetic tail.
3.1
K-3
K-3
Keywords: Artificial limbs -- Juvenile literature; Bottlenose dolphin -- Wounds and injuries -- Juvenile literature; Tail -- Surgery -- Juvenile literature; Artificial limbs; Bottlenose dolphin -- Wounds and injuries; Tail -- Surgery; Artificial limbs; Bottlenose dolphins -- Wounds and injuries; Tail -- Surgery